Urgensi Kerja Sama Tentara Nasional Indonesia Dan Forcas Defese Timor Lorosae Dalam Penanggulangan Perdagangan Ilegal Lintas Batas Antara Indonesia Dan Timor Leste - Vinsensius Tamelab; Mericiana Yulita Fin Tae; Yohanes Arman; Yustinus Pedo (Universitas Maritim AMNI Semarang, 2023)
The issue of state borders is not only related to state borders but includes land borders, sea borders and air borders which related to economic problems which have an impact on cross-border illegal trade. One of the national borders that has been attracting attention is the border between Indonesia and East Timor. The problem so far has been the increase in illegal trade, particularly the smuggling of fuel oil (BBM). Considering that the problems that occur in the border area are quite complex, it is necessary to have cooperation between the Indonesian National Armed Forces and the East Timor Defense Force to tackle illegal trade that occurs in the Indonesian border area of Timor Leste. Law No. 4 of 2015, is one of the legal instruments that regulates cooperative relations between Indonesia and the Democratic Republic of Timor Leste, especially in the field of defense and security. The implementation of Law No. 4 of 2015 is by entering into an agreement to form a Joint Border Committee (JBC) institution between Indonesia and East Timor. Forms of cooperation from this committee consists of solid line of communication and coordination between the security forces of the two countries, carrying out joint patrols, improving facilities and infrastructure, efforts to strengthen the integrity of each country, building synergies with local governments in border areas, building cooperation in an effort to help reduce illicit business activities and border crossers through the narrow road which has a positive impact on the national stability of the two countries.